TOPICAL ISSUES OF INVESTING IN INNOVATIVE PROJECTS - Yusupov Nematillo , Saidturaevich (THE INNOVATION ECONOMY, 2025)
Innovation in the modern economy is considered as one of the main drivers of economic growth. In order to achieve economic growth on the basis of competitiveness, such goals as the organization and development of high tech production, the effective use of resources, investing in innovative projects is becoming a necessity. Therefore, innovation is becoming an important component of development and economic growth at the present stage of the development of our country. Therefore, the study and analysis of the effectiveness of investments for innovative projects is of strategic importance today. This article discusses scientific approaches to assessing the investment efficiency of innovative projects.